Laplace Pressure Difference Enhances Droplet Coalescence Jumping on Superhydrophobic Structures - Liu, Chuntian (Langmuir : the ACS journal of surfaces and colloids, 2022)
Coalescence-induced droplet jumping has great prospects in many applications. Nevertheless, the applications are vastly limited by a low jumping velocity. Conventional methods to enhance the droplet coalescence jumping velocity are enabled by protruding structures with superhydrophobic surfaces. However, the jumping velocity improvement is limited by the height of protruding structures. Here, we present rationally designed limitation structures with superhydrophobic surfaces to achieve a dimensionless jumping velocity, Vj* ≈ 0.64. The mechanism of enhancing the jumping velocity is demonstrated through the study of numerical simulations and geometric parameters of limitation structures, providing guidelines for optimized structures. Experimental and numerical results indicate that the mechanism consists of the combined action of the velocity vectors' redirection and the Laplace pressure difference within deformed droplets trapped in limitation structures. On the basis of previous research on the mechanisms of protruding structures and our study, we successfully exploited those mechanisms to further improve the jumping velocity by combining the limitation structure with the protruding structure. Experimentally, we attained a dimensionless jumping velocity of Vj* ≈ 0.74 with an energy conversion efficiency of η ≈ 48%, breaking the jumping velocity limit. This work not only demonstrates a new mechanism for achieving a high jumping velocity and energy conversion efficiency but also sheds lights on the effect of limitation structures on coalescence hydrodynamics and elucidates a method to further enhance the jumping velocity based on protruding structures